Diagnostic and Developmental Potentials of Dynamic Assessment for L2 writing. (30th July 2015) - Rahimi, Mohammad; Kushki, Ali; Nassaji, Hossein
Abstract : Many theoretical claims have been made about the role and effectiveness of Dynamic assessment (DA) in L2 learning. It has, for example, been suggested that this kind of approach provides learners with appropriate and timely feedback in a supportive and interactive environment and in ways that can maximize L2 development (Poehner & Lantolf, 2013). However, issues remain about how to measure the effects of DA and how these effects compare with those of traditional ways of providing feedback. This qualitative case study explores the role of interactional DA in the development of L2 writing skills. Three advanced EFL students each produced first 10 writing samples in ten individualized writing sessions. They then engaged in 10 collaborative tutorial sessions with their teacher and received feedback based on the DA principles. The interactions were recorded, transcribed, and analyzed. The results revealed important diagnostic and treatment effects for interactive DA.